Análise das condições de vida no território rural Planície Litorânea no Estado do Piauí - Lima, Maria de Jesus Gomes de (2014)
The term living conditions is a highly subjective concept, since, in their design, are aspects of the provision of basic necessities of life. The under-standing the needs of these individuals to ensure better living conditions and well-being. Therefore, the condition of life refers to the external subject who provide their well-being factors. So no need to evaluate public policies for the development, it is having an effect on the view of the producer Coastal Plain Rural Planning. This study aimed to examine the living conditions in rural areas Coastal Plain, as well as their socioeconomic characterization, verification of factors, characteristics and effects of development in the area and the living conditions index (LCI). As methodology, the data used in this study were obtained with the use of questionnaires with rural households, to identify, according to the perceptions of local actors, the Condition Index (LCI). For construction of Condition Index (LCI) used the excel and IBM SPSS to analyze the socioeconomic characteristics. Among the main results, it can be noted that the population is characterized with quantity of members per family which is the national average; the illiteracy rate is high (50%); sanitation conditions are poor and access to drinking water as well. There was economic improvements, with noticeable because of access to consumer goods and increased income; found two types of households: with production and no production, where the ICV obtained in the territory was 0,491 (households with production) and 0,537 (households without production), both considered Midi according to calculation basis of the Ministry of Agrarian Development (MDA). The variable with the greatest contribution was the residence of the families on the farm (20.6%). Therefore it is concluded that the public territorial development policies are having effects, according to the perception of the producers inserted in rural areas Coastal Plain.